Application of Conceive, Design, Implement and Operate (CDIO) Strategy for the Development of Engineering Education in Indian Perspective. Issue 1 (January 2023) - Lenin, N.; Siva Kumar, M.; Selvakumar, G.
Indian education system has faced many reforms and changes right from Gurukula education system in Vedic age to the present outcome-based education system. There lies a wide gap between industries and institutions in India due to the lagging of quality graduates. To bridge the gap, the outcome-based education system has been implemented widely in India. Still, an effective approach that reforms the education system is needed to fulfill the needs of industries. Worldwide, large numbers of universities have adopted Conception, Design, Implementation, and Operation (CDIO) approach in view to produce quality graduates. At this juncture, it is required to analyze and evolve the fruitful strategies in implementation of CDIO approach in Indian engineering education scenario. In the present work, the need of CDIO implementation has been critically analyzed and presented. Furthermore, the present Indian engineering education system has been analyzed on various levels. The implementation strategies have been proposed in two categories as macro and micro levels that are required by the government bodies. The requirements for implementing CDIO are briefed based on institution, faculty and students levels. In addition, the bottlenecks in implementation of CDIO are studied, and the tactics to overcome the same are also discussed elaborately.